Álgebra de caminhos generalizada e uma representação para k-álgebras de dimensão finita - Fernando dos Reis Naves (2017)
This work has two goals. The first one is to introduce the concept of generalized path algebra of the article [7] and present some results from it. The second one is to develop a result that realizes every finite dimensional K-algebra as a quocient of a generalized path algebra whose vertices are simple algebras by a "well behaved"ideal.